Emerging Variants of the Integrative and Conjugant Element ICEMh1 in Livestock Pathogens: Structural Insights, Potential Host Range, and Implications for Bacterial Fitness and Antimicrobial Therapy - Cameron, Andrew; Zaheer, Rahat; McAllister, Tim A. (Frontiers in Microbiology, 2019)
Horizontal gene transfer of integrative and conjugative elements (ICE) in bacterial pathogens of the bovine respiratory disease (BRD) complex has emerged as a significant cause of antimicrobial resistance (AMR) and therapeutic failure and mortalities in cattle. The aim of this study was to assess an AMR ICE occurring in Pasteurella multocida from a case of BRD, designated ICEMh1PM22 for its structure and host genome insertion site, and to identify consequences for host fitness and antimicrobial therapy. The modular structure of ICEMh1-like elements found in several related livestock pathogens was compared to ICEMh1PM22, and the repertoire of cargo genes in variable ICE modules was functionally categorized. AMR genes were identified as frequent additions to the variable modules of ICEMh1-like elements. Random PCR-based mapping of ICEMh1PM22-genome junctions in transconjugants provided evidence that ICEMh1PM22 integrates into the tRNA-leu for the UUG codon, and not into tRNA-leu for other codons. This was separately confirmed in the genomes of ICEMh1-like-harboring livestock pathogens. Bacterial genera harboring receptive tRNA-leuUUG were identified to establish the potential host range of ICEMh1-like elements. ICEMh1PM22-carrying transconjugants in P. multocida and Mannheimia haemolytica were less fit than isogenic strains without the ICE when grown without antimicrobial selection. This fitness cost was abrogated in the presence of subinhibitory concentrations of antimicrobials. Despite this cost, ICEMh1PM22 was retained in transconjugants in extended culture. To identify possible therapeutic efficiencies, antimicrobial combinations were screened for synergistic interactions against AMR ICEMh1PM22-carrying transconjugants. No antimicrobial combination tested exhibited synergistic interactions against AMR P. multocida or M. haemolytica harboring ICEMh1PM22. In conclusion, this study provided information on the structural variation of ICEMh1-like elements, refined the ICE insertion site and potential host range, and demonstrated the risk and consequences for AMR following horizontal transfer of ICE into BRD pathogens.